Murder in the middle pasture - Erickson, John R., 1943- (Erickson, John R., 1943- Hank the Cowdog, 1991)
When a calf is murdered, Hank, the wiley Cowdog and Head of Ranch Security, pursues a gang of wild dogs and a clan of coyotes to find the killer.